Fluvial inverse modeling for inferring the timing of Quaternary uplift in the Simbruini range (Central Apennines, Italy). Issue 5 (19th August 2021) - Delchiaro, Michele; Fioramonti, Veronica; Della Seta, Marta; Cavinato, Gian Paolo; Mattei, Massimo
Abstract: The timing of Quaternary uplift evolution of the Simbruini range (Central Apennines, Italy) is poorly known due to the lack of reliable chronological constraints of the post‐orogenic continental clastic units, deposited after the upper Messinian thrust‐top facies, and tectonic events. In this regard, we identified the main geomorphic markers, including several levels of continental units, whose plano‐altimetric projection along the river longitudinal profile has been correlated with the main non‐lithological knickpoints. Furthermore, we inferred the uplift history of the range by applying the inverse modeling of the river longitudinal profiles. Assuming a block uplift model, the drainage network cutting the Simbruini range recorded 2.4 ± 0.5 Ma of tectonic history, characterized by variable base‐level fall rates (corresponding to variable uplift rates).